Case Report: Malignant Primary Sellar Paraganglioma With Unusual Genetic and Imaging Features - Stojanoski, Stefan; Boldt, Henning Bünsow; Kozic, Dusko; Patócs, Attila; Korbonits, Márta; Medic-Stojanoska, Milica; Casar-Borota, Olivera (Frontiers in Oncology, 2021)
Background Paraganglioma occurs rarely in the sellar/parasellar region. Here, we report a patient with malignant paraganglioma with primary sellar location with unusual genetic and imaging features. Case Presentation A 31-year-old male presented with mild hypertension, headache, nausea, and vomiting. A sellar/parasellar tumor mass was revealed by magnetic resonance imaging (MRI), while an endocrine work-up found partial hypopituitarism, suggesting that it was a non-functioning pituitary tumor. Antihypertensive therapy and hormone replacement were initiated. Tumor reduction was achieved with transsphenoidal neurosurgery. However, histological diagnosis was not possible due to extensive tissue necrosis. After 4 years of stable disease, the residual tumor showed re-growth requiring gamma knife radiosurgery. Four years after the radiosurgery, MRI showed a significant tumor progression leading to a second neurosurgery. This time, pathological and immunohistochemical findings revealed paraganglioma. Plasma levels of metanephrine and normetanephrine were normal. A gene sequencing panel performed on DNA extracted from blood excluded germline mutations in 17 susceptibility genes. The patient developed new tumor masses in the neck, and the third surgery was performed. Immunohistochemistry demonstrated lack of ATRX (alpha thalassemia/mental retardation syndrome X-linked) protein in tumor cells, indicating an ATRX gene mutation. Molecular genetic analysis performed on tumor DNA revealed a combination of ATRX and TP53 gene abnormalities; this was not previously reported in paraganglioma. MRI and 68Ga-DOTANOC PET/CT revealed the full extent of the disease. Therapy with somatostatin LAR and 177Lu-DOTATATE Peptide Receptor Radionuclide Therapy (PRRT) was initiated. Conclusion Although rare, paraganglioma should be considered in the differential diagnosis of sellar/parasellar tumor lesions, even in the absence of typical imaging features. ATRX gene mutation in paraganglioma is an early predictor of malignant behavior and a potential novel therapeutic marker when pharmacological therapy targeting mutated ATRX becomes available.